Pathogens in ornamental waters: a follow up study - Duarte, Maria (2017)
Ornamental waters of easy access and populated with animals are quite attractive and can hide threats to human health. Here we evaluated the microbiota of ornamental waters in a Lisbon park. Water and biofilm samples where collected, in 2 lakes (L1-L2) and ornamental fountains (L3-L4) in February/2015. In May/2015 and monthly during a year (starting March/2016) samples from L4 where collected. Microbiota identification was performed as described previouslya. Biofilm assembly was monitored by crystal violet assay and SEMb and antibiotic susceptibility was performed by conventional methods. The results of the first water sampling (Feb/2015) revealed the presence of Enterobactereaceae and non-fermentative oxidase-positive bacteria. Fountains and lakes presented different microbota being the highest diversity found in L1 hosting a duck population. This result suggested the existence of an interplay between animal inhabitants and microbiota which was confirmed by the second sampling of L4 (May/2015). Between the 2 sampling events a fish population was introduced and the microbiota was completely altered with the appearance of a typical fish pathogen (Aeromonas spp). This tendency was also confirmed over 2016. K. pneumoniae and Aeromonas spp., present as planktonic and biofilm organized bacteria in 2015 showed an enhanced ability to assemble biofilms in vitro at 25 °C than at 37 °C. Bacteria recovered from biofilm showed an increased antibiotic resistance compared to planktonic counterparts. The pilot study conducted during 2015 and the follow up study (still in progress) support a periodic control of ornamental water microbiota as simple preventive measure to avoid potential health issues.